Privatized Returns and Socialized Risks: CEO Incentives, Securitization Accounting and the Financial Crisis - Michele Fabrizi; Antonio Parbonetti (City, University of London, City Political Economy Research Centre (CITYPERC), 2013)
The paper investigates the role of CEO's equity and risk incentives in boosting securitization in the financial industry and in motivating executives to reduce the perceived risk while betting on it. Using a sample of US financial institutions over the period 2003-2009 we document that CEOs with high equity incentives have systematically engaged in securitization transactions to a larger extent than CEOs with low incentives. We also show that CEOs with high equity and risk-related incentives have engaged in the securitization of risky loans and have used securitization for transferring risks to outside investors. Finally, we show that executives incentivized on risk have provided outside investors with low quality disclosure about losses recorded on securitized loans thus contributing to increase the opacity of securitization transactions undertaken. Overall, we interpret our results as evidence that CEOs have foreseen in securitizations under US GAAP an opportunity for hiding risks while bearing them and generating profits and cash flows because of the risks. Our results are robust to several model specifications as well as to endogeneity concerns.
Keywords: 330; Executive compensation; CEO incentives; Securitization; Financial Crisis